2020
DOI: 10.1155/2020/2358391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Fat Diet and Exercise Intervention on the Metabolism Regulation of Infant Mice

Abstract: Maternal exercise is crucial for promoting the health of the offspring. Previous studies showed that long-term maternal exercise improves energy metabolism during pregnancy. Whether swimming exercise can reverse the metabolic disorders caused by high-fat exposure in the early life of the offspring is yet to be elucidated. Three-week-old C57BL/6 female mice were randomly assigned to the standard chow diet group (SC), standard chow diet and exercise group (SC-Ex), high-fat diet group (HFD), and high-fat diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These studies are based on the “developmental overnutrition hypothesis” that explains the association between mother and child's obesity. According to Armitage et al ( 29 ), higher circulating levels of glucose, free fatty acids (FFA), amino acids, ( 29 ) fetal insulin ( 16 ), and digestive hormones ( 33 ) in the mother cause a permanent alteration of appetite control and energy metabolism in the fetus. Further, this is transferred to the next generation through inheritance.…”
Section: Complications Of Maternal Obesity In the Mothermentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are based on the “developmental overnutrition hypothesis” that explains the association between mother and child's obesity. According to Armitage et al ( 29 ), higher circulating levels of glucose, free fatty acids (FFA), amino acids, ( 29 ) fetal insulin ( 16 ), and digestive hormones ( 33 ) in the mother cause a permanent alteration of appetite control and energy metabolism in the fetus. Further, this is transferred to the next generation through inheritance.…”
Section: Complications Of Maternal Obesity In the Mothermentioning
confidence: 99%
“…In a separate study in infant mice, the protective effect of maternal aquatic exercise from an obesogenic diet was assessed ( 33 ). Three-week-old maternal mice were put on either a CD (12% fat) or HFD (45% fat) and subsequently divided into CD-sedentary (CD-sed), CD-exercise, HFD-sedentary, and HFD-exercise for 13 weeks before conception and for the entire length of gestation.…”
Section: Exercise Studies In Animal Modelsmentioning
confidence: 99%
“…Aparicio et al showed that exercise during pregnancy reduces the release of proinflammatory cytokines such as TNF- α , IL-8, and IL-6 in colostrum and mature human milk [ 16 ]. Zhu et al demonstrated that maternal exercise reduced the expression inflammatory factors in the male offspring mice [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of maternal exercise intervention in obese pregnancy have been carried out in rodent models. Although there is some variation in the nature of the intervention with different studies utilising voluntary or involuntary wheel running (48,(222)(223)(224)(225)(226)(227)(228)(229)(230) , treadmill running (128,(231)(232)(233)(234)(235) or swimming (236) , some consistent patterns have emerged in terms of maternal and offspring outcomes.…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%
“…In the offspring, the elevated blood glucose and insulin levels seen in both male and female offspring of obese rodent dams can be improved in the pup (223) and adult offspring (48,222,(225)(226)(227)(228)231,234,236) by exercise intervention during pregnancy. Maternal exercise intervention is also protective against other adverse effects of maternal obesity in rats and mice, including preventing increased adiposity (225,234,236) , cognitive impairment (229) , dysregulation of hypothalamic gene expression (48) , hepatic dysfunction and insulin resistance (226) , epigenetic and transcriptional changes in skeletal muscle leading to impaired muscle oxidative capacity (223,227,228) , increased inflammation (48) and β-cell dysfunction (230) . However, few studies have specifically investigated the effects of exercise intervention in obese pregnancy on offspring cardiovascular function (128) .…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%